Karakter Seleksi pada Generasi Awal untuk Adaptasi Padi terhadap Cekaman Suhu Tinggi - Manalu, Victor Manotar Pademan; Wirnas, Desta; Sudarsono, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
ABSTRACT Developing new rice varieties adaptive to heat stress is important to maintain high rice production in anticipating global warming effects. This research was aimed to find selection characters and to select the best segregant in early generation based on agronomic characters for adaptation of rice to heat stress. The experiment was carried out in September 2014 to Januari 2015. About 210 F2 segregants generated trough hybridization between IPB 4S (sensitive parent) and Situ Patenggang (tolerant parent), 20 individuals of IPB 4S, and 20 individuals of Situ Patenggang, were used as genetic control. All genetic materials were exposed to high temperature stress by growing in a green house of Bogor Agricultural University. The average temperature in the research period was 24 °C and 42.09 °C, respectively for minimum and maximum temperature. The results showed that charachters of productive and total tiller number, total grain number, and seed weight had high heritability, high coeffiecient of genetics variability-with an additive gene action. That charachters could be proposed as selection criteria in early generation for rice breeding of adaptation to high temperature stress. The characters could be applied in either single trait or multiple traits selection. Based on multiple traits selection we found 50 the best F2 segregation.Keywords: differential selection, early generation, heat tolerant, heritability, gene action, variability genetics coeffiecient